The effect of increasing operating cash flow on financial liquidity of PT Garuda Indonesia - Angela Stefani Isweri; Elizabeth Tiur Manurung (Proceeding International Conference on Accounting and Finance, 2023)
The Cash Flow Statement is a description of the activities in the company so it automatically can see how the company manages financial turnover and the ability to pay its obligations. Liquidity is very important because if the company is not liquid, it will be difficult to pay its obligations. There are three activities, one of which is Operational Activities, that will be used in this study. The company under study is PT. Garuda Indonesia Tbk. Thus, this study aims to see how much an increase in Operating Cash Flow can affect the Liquidity of the Garuda Indonesia company. This research used The Hypothetical-Deductive Method with the regression method used, Single Regression. The result is that the increase in operating cash flow has a significant effect on alpha by 10%. In accounting, with this increase, the company is able to pay the obligations owned by the company.